MODEL PREDIKSI PENERIMA BANTUAN SOSIAL BERBASIS ALGORITMA RANDOM FOREST - Sukma, Siti Hatmara; Suarna, Nana; Bahtiar, Agus; Marta, Puji Pramudya; Anam, Khaerul (Jurnal Rekayasa Perangkat Lunak dan Sistem Informasi, 2026)
Inaccurate targeting of social assistance beneficiaries remains a critical issue at the village level due to subjective and inconsistent manual verification processes. This study aims to develop a predictive model for determining social assistance eligibility using the Random Forest algorithm based on 2021 SDGs Village microdata from Cibeureum Village. The research involves data preprocessing, model training, and hyperparameter optimization, with performance evaluation using accuracy, precision, recall, and F1-score metrics. The proposed model achieved an accuracy of 94.34%, indicating strong and stable classification performance. Feature importance analysis shows that housing conditions, access to clean water, and asset ownership are the most influential socioeconomic indicators. These findings demonstrate that Random Forest can effectively support data-driven decision-making and improve the accuracy of social assistance distribution at the village level.